(untitled) (Transactions of the Association of European Schools of Planning, 2021)
The Taiwanese central government views city-county consolidations as an effective method to strengthen national competitiveness and to balance regional development. But for local governments, consolidation presents a series of planning challenges, especially in relation to the reconstruction of planning concepts and discourses in their new territories. Aiming to understand the process, this study first proposes a typology of regional planning concepts as a conceptual tool to explore whether and how the consolidated governments (re)construct their urban-rural planning concepts, and then it examines the factors that may influence (re)conceptualisation through a comparative study of Taichung City and Tainan City. The research results show that overemphasis on using the concept of competitive city regionalism to balance regional development at the national level may lead to a widening of rural-urban disparities at regional and local levels.